2016
DOI: 10.1007/s11661-016-3366-1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ni and V Trace Elements on High-Temperature Tensile Properties and Aging of A356 Aluminum Foundry Alloy

Abstract: High-temperature tensile properties of unmodified A356 alloy with and without the addition of Ni or V in traces (600 and 1000 ppm of Ni and V, respectively) were investigated by analyzing samples obtained from sand and permanent mold castings in the as-cast and T6 heat-treated conditions. Tensile tests were performed at 508 K (235°C) at a crosshead speed of 1 mm/min. In addition, samples were subjected to artificial aging at 508 K (235°C) for different times, and corresponding hardness curves were plotted. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In the low-temperature section, strength and hardening rate of the alloy increase with the plasticity and ductility decreasing, leading to higher stress state and increased number of fractured silicon particles [20]. In high-temperature section, the matrix is more prone to deform [4], due to the lower elongation, the eutectic Si particles cannot produce such a large deformation as the matrix, leading to a large proportion of silicon particles fragmenting to pieces in the high-temperature section [21]. In addition, in the low-temperature section, many eutectic silicon particles dominate the path of crack propagation; however, in the high-temperature section, fragmented eutectic silicon particles cannot change the propagation path of the cracks, and the cracks can propagate relatively freely, which is the reason for fracture profile micromorphology differences at different temperatures.…”
Section: Fracture Morphology Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the low-temperature section, strength and hardening rate of the alloy increase with the plasticity and ductility decreasing, leading to higher stress state and increased number of fractured silicon particles [20]. In high-temperature section, the matrix is more prone to deform [4], due to the lower elongation, the eutectic Si particles cannot produce such a large deformation as the matrix, leading to a large proportion of silicon particles fragmenting to pieces in the high-temperature section [21]. In addition, in the low-temperature section, many eutectic silicon particles dominate the path of crack propagation; however, in the high-temperature section, fragmented eutectic silicon particles cannot change the propagation path of the cracks, and the cracks can propagate relatively freely, which is the reason for fracture profile micromorphology differences at different temperatures.…”
Section: Fracture Morphology Analysismentioning
confidence: 99%
“…In the past few decades, due to its lightweight, excellent mechanical performances, good corrosion resistance and castability, hypoeutectic Al-Si casting alloy, especially Al-Si-Mg alloys, were widely used in automotive engines, high-speed train sleepers and other transportation fields [1][2][3]. It is known that automotive engines operated at the temperature of up to 200 • C [4], and the service temperature of high-speed train sleeper materials may reduce to −60 • C in northern China [5]. However, Al-Si-Mg alloy will lose its strength above 150 • C [6] and generate low-stress fracture due to local plastic deformation caused by stress concentration at low temperatures [7], leading to the demand for expanding its operating temperature range from −60 • C to 200 • C [8].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the effect of secondary phases (i.e., iron intermetallic compounds), interesting analyses can be found in the work of Shabestari et al [56]. This is particularly interesting since numerous studies have reported the correlation between amount and morphology of secondary phases, for instance, intermetallic ones containing Fe, Mn, Cr, Ni, and mechanical properties [76][77][78][79][80] for casting Al-Si alloys. In particular, these authors found that the peculiar microstructural characteristics of the thixoformed alloy, such as the extremely low porosity, fine and equiaxed morphology of the α-Al grains and uniform distribution of intermetallic compounds fragmented by the process route, enhance strength and elongation, in comparison with the as-cast condition.…”
Section: Tensile Behaviormentioning
confidence: 99%
“…As-cast condition: Addition of transition metals to Al-Si alloys results in the formation of different TM-rich phases in the as-cast microstructure [4,7,8]. Unlike typical Mg-and Cu-bearing phases, TM-rich phases have a melting point higher than the melting point of the eutectic phase [7,9].…”
Section: Introductionmentioning
confidence: 99%